Pollen morphology of ornamental plants - Alicia Maria Landfeldt; Denise M. D. da S. Mouga (Acta Biológica Catarinense, 2026)
Pollen grains are reproductive structures with an inner wall (intine) and an outer wall (exine), related to the time required for their maturation until the germination of the pollen tube. These two walls present the morphological components used in palynological characterization. There is a lack of palynological studies for ornamental plant species in Joinville (SC). Thus, ornamental plant species without pollen descriptions from Joinville were collected. Closed buds were removed, preserved in acetic acid, the pollen grains were acetolysed and light microscopy slides were prepared. SEM images were also taken. Measurements, apertures, exine ornamentation, shape, symmetry, and amb were evaluated. The pollen morphology of the species Angelonia minor (Plantaginaceae), Calliandra brevipes (Fabaceae), Unxia kubitzkii (Asteraceae), and Myrceugenia campestris (Myrtaceae) was analyzed. The pollen grains of Plantaginaceae, Asteraceae, and Myrtaceae are in monads, radially symmetrical, isopolar, while those of Fabaceae are in polyads with irregular symmetry, heteropolar. A. minor has small grains, 3-colporate, suboblate, circular, microverrucate/microfossulate perforated; C. brevipes, very large, porate, psilate/microverrucate; U. kubitzkii, large, 3-colporate, oblate-spheroidal, circular, echinate; M. campestris, small, 3-colporate, oblate, psilate.